The power of human : how our shared humanity can help us create a better world - Waytz, Adam (W.W. Norton & Company, 2019)
Arguing that modern technology has provided unprecedented access to others while ironically promoting human disengagement, a respected social psychologist shares recommendations for rehumanizing life in relationships and the business world.